The Effect of Profitability, Earning Per Share, Price Book Value on Share Prices Mediated by Dividend Payout Ratio - J Indah Perdana Sri Rahayu; Cepi Pahlevi; Andi Aswan (Magister Management, Hasanuddin University, 2021)
The current development of the capital market represents an important development for the Indonesian economy. This occurs due to the increasing public interest in the capital market, the increasing number of companies registered in the capital market, and government support through investment policies. This could be achieved by maximizing the market value of the share price concerned. The purpose of this study was to determine and analyze the effect of ROE, EPS, PBV on DPR, to analyze the effect of ROE, EPS, PBV, and DPR on stock prices, DPR on stock prices, the effect of ROE, EPS, and PBV on stock prices through DPR. The technique of collecting data is through documentation, with data analysis techniques using descriptive analysis of research variables, descriptive statistics, classical assumption tests, multiple regression analysis, and path analysis. The results of the study found that ROE, EPS, and PBV had a positive and significant effect on the dividend payout ratio. The ROE has a negative and significant effect on stock prices, while EPS, PBV, and DPR have a positive and significant effect on stock prices. However, the dividend payout ratio cannot mediate the effect of profitability (ROE) on stock prices. The dividend payout ratio can mediate the effect of earnings per share and price-book value on stock prices.